2007
DOI: 10.1590/s0102-33062007000300012
|View full text |Cite
|
Sign up to set email alerts
|

Novas referências de hepáticas (Marchantiophyta) da Floresta Nacional de Caxiuanã para o Estado do Pará, Brasil

Abstract: São apresentadas no presente trabalho oito hepáticas referidas pela primeira vez para o Estado do Pará, sendo cinco delas novas referências também para a região Norte do país. Todas são provenientes da Estação Científica Ferreira Penna (ECFPn) (1º42'30"S e 51º31'45"W), localizada na Floresta Nacional de Caxiuanã (Flona Caxiuanã, Amazônia Oriental). São elas Ceratolejeunea desciscens (Sande-Lac.) Schiffn., Colura greig-smittii Jovet-Ast, Lejeunea raddiana Lindenb. Gottsche, Rectolejeunea emarginuliflora (Gottsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
1
2
0
2
Order By: Relevance
“…1), representing approximately 31% of the known bryophyte flora in the state of Pará (Costa 2013). The species richness found in Capitão Poço was similar to that reported for other upland forests in the state, such as that within Caxiuanã National Forest, where 126 bryophyte species have been recorded (Lisboa & Nazaré 1997, 2002Ilkiu-Borges & Lisboa 2002d;Alvarenga et al 2007). In Capitão Poço, we identified 62 (49.2%) of those 126 species.…”
Section: Overall Species Richnesssupporting
confidence: 84%
“…1), representing approximately 31% of the known bryophyte flora in the state of Pará (Costa 2013). The species richness found in Capitão Poço was similar to that reported for other upland forests in the state, such as that within Caxiuanã National Forest, where 126 bryophyte species have been recorded (Lisboa & Nazaré 1997, 2002Ilkiu-Borges & Lisboa 2002d;Alvarenga et al 2007). In Capitão Poço, we identified 62 (49.2%) of those 126 species.…”
Section: Overall Species Richnesssupporting
confidence: 84%
“…The identification of the samples was based on the work of Yano (1975), Vital (1980), Reese (1993), Gradstein (1994), Sharp et al (1994), Buck and Goffinet (2000), Crandall-Stotler and Stotler (2000), Buck (2003), Gradstein and Costa (2003), Stotler and Crandall-Stotler (2005), Alvarenga et al (2007), Pursell (2007); and compared to the samples identified by experts previously.…”
Section: Methodsmentioning
confidence: 99%
“…Since then, the number of bryologic inventories has increased in the last years (Glime 2006, Alvarenga et al 2007. Today, 479 species are listed to Cerrado, and 309 of these species to Goiás State (Yano & Costa 2000, Gradstein et al 2005, Yano & Peralta 2007, Yano & Peralta 2008, Costa 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Estas novas referências estão tratadas detalhadamente em Alvarenga et al (2007). A seguir é apresentada a lista das espécies identificadas (as que estão assinaladas com asterisco são as novas referências para o estado do Pará).…”
Section: Brioflora Identificadaunclassified
“…O assinalamento de oito táxons inéditos para o Estado (Alvarenga et al, 2007) é evidência de que o estudo cumpriu seu objetivo, que era primordialmente contribuir para o conhecimento da brioflora amazônica. O estudo, ademais, confirma que a brioflora da Amazônia abriga uma diversidade e riqueza dignas de serem melhor exploradas.…”
Section: Conclusõesunclassified